Screening fifth forces in scalar-vector-tensor theories - Gonzalez Espinoza, Manuel (2024)
We study a screening mechanism in the context of scalar-vector-tensor (SVT) theories. Thisscreening mechanism is based on both the derivative self-interactions of the vector field and theinteractions of the scalar field with the vector field and curvature. We calculate the field equationsin a spherically symmetric space-time, and then, we study the conditions for which this mechanismis successful in a weak gravitational background. In order to corroborate these analytical results,we have performed a numerical integration of the full equations. Finally, the corrections to thegravitational potentials have also been computed. We conclude that the present model, includingboth kinds of interactions, can avoid the propagation of the additional longitudinal mode arisingin these theories. We also show that the space parameter of the model is compatible with solarsystem constraints. This result extends the previous one found in the literature for generalizedProca theories to the case of SVT theories in the presence of scalar-vector interactions.